A Molecular Placeholder Strategy To Access a Family of Transition‐Metal‐Functionalized Vanadium Oxide Clusters. Issue 38 (31st July 2014) - Kastner, Katharina; Margraf, Johannes T.; Clark, Timothy; Streb, Carsten
Abstract Systematic access to metal‐functionalized polyoxometalates has thus far been limited to lacunary tungsten oxide and molybdenum oxide clusters. The first controlled, stepwise bottom‐up assembly route to metal‐functionalized molecular vanadium oxides is now presented. A di‐vacant vanadate cluster with two metal binding sites, (DMA)2[V12O32Cl]3− (DMA=dimethylammonium) is formed spontaneously in solution and characterized by single‐crystal X‐ray diffraction, ESI mass spectrometry, 51V NMR spectroscopy, and elemental analyses. In the cluster, the metal binding sites are selectively blocked by hydrogen‐bonded DMA placeholder cations. Reaction of the cluster with transition metals TM (Fe3+, Co2+, Cu2+, Zn2+) gives access to mono‐functionalized vanadate clusters (DMA)[TM(L)V12O32Cl]n− (L=ligand). Metal binding is accomplished by significant distortions of the vanadium oxide framework reminiscent of a pincer movement. Cluster stability under technologically relevant conditions in the solid‐state and solution is demonstrated.